Production of lactic acid from kenaf core hydrolysate by rhizopus oryzae FTCC 5215 - Seeni Mohamed, Nurhafizah; Anuar, Hazleen; Mel, Maizirwan; Othman, Rashidi; Mohd Norddin, Nur Aisyah; Mohd Nasir, Nur Aimi (Trans Tech Publications, Switzerland, 2012)
Lactic acid (LA) is commercially produced biologically using food-derived raw materials such as potato and corn. It seems to be less economical since they have to compete with the food sources industries. Thus, kenaf (Hibiscus cannabinus) is found to be the best alternative to substitute the raw material for LA production. In this paper, kenaf core were used as the substrate for production of LA by Rhizopus oryzae FTCC 5215. Since kenaf is one type of lignocellulosic material which is naturally resistant to breakdown to its structural sugars, it will inhibit microorganisms to be accessed through. Thus, hydrolysis process is needed as the aid for the liberation glucose. The highest value of lactic acid produced is 15.2 g/L at 25 oC with speed 200 rpm.